TEST 77 Examination of Self-Rated Health, Psychological Well-Being and Cardiovascular Health Risks – 10-Year Follow-Up of the Budakalász Epidemiological Study in Hungary - Ehrenberger, Blanka; Ocsovszky, Zsófia; Assabiny, Alexandra; Otohal, József; Papp, Magor; Borenszki-Gutási, Éva; Bagyura, Zsolt; Csabai, Márta (European Journal of Mental Health, 2026)
Introduction: Self-rated health (SRH) predicts morbidity and mortality; however, its long-term trajectories and associations with psychological wellbeing (PWB), health behaviors, and cardiovascular risk remain understudied in Central and Eastern Europe. Aim: To describe 10-year changes in cardiovascular risk, health behaviors, PWB, and SRH, and to examine how SRH relates to PWB, health behaviors, and cardiovascular risk in a non-clinical Hungarian adult sample. Methods: Adults from Budakalász who participated in a cardiovascular screening in 2012 were invited to follow up in 2023. The analysis included 170 participants aged 45–65 years without major cardiovascular events. SRH was assessed with a single global item. Anthropometric and laboratory measures, FINDRISK and Framingham risk scores, health behaviors, and a fouritem PWB score derived from the Short Form (36) Health Survey (SF-36)were included. Non-parametric tests, independent sample t-tests, and Spearman correlations were applied. Results: Over the 10-year period, SRH showed a modest overall decline, with approximately one-quarter of participants reporting deteriorated SRH, more than half remaining stable, and a minority improving. SRH trajectories were not consistently associated with changes in PWB, cardiovascular risk, or health behaviors. Cross-sectionally, SRH was moderately correlated with PWB but only weakly related to health behaviors. Anthropometric data and cardiovascular risk scores increased, whereas fasting glucose, HbA1c%, and fruit and vegetable consumption improved, and physical activity shifted toward lower intensity. Conclusions: SRH was closely aligned with PWB over 10 years but largely decoupled from objective cardiovascular risk and health behaviors, supporting SRH as a psychologically grounded subjective health construct relevant for cardiovascular prevention.